Cationic surfactants as antifungal agents - Fait, María Elisa (2019)
Fungi-in being responsible for causing diseases in animals and humans as well as environmental contaminations in health and storage facilities-represent a serious concern to health security. Surfactants are a group of chemical compounds used in a broad spectrum of applications. The recently considered potential employment of cationic surfactants as antifungal or fungistatic agents has become a prominent issue in the development of antifungal strategies, especially if such surface-active agents can be synthesized in an eco-friendly manner. In this review, we describe the antifungal effect and the reported mechanisms of action of several types of cationic surfactants and also include a discussion of the contribution of these surfactants to the inhibition of yeast-based-biofilm formation. Furthermore, the putative mechanism of arginine-based tensioactive compounds as antifungal agents and their applications are also analyzed.